Connectivity Indices of Intuitionistic Fuzzy Graphs and Their Applications in Internet Routing and Transport Network Flow. (14th August 2021) - Naeem, Tulat; Gumaei, Abdu; Kamran Jamil, Muhammad; Alsanad, Ahmed; Ullah, Kifayat
Abstract : Connectivity index CI has a vital role in real-world problems especially in Internet routing and transport network flow. Intuitionistic fuzzy graphs IFGs allow to describe two aspects of information using membership and nonmembership degrees under uncertainties. Keeping in view the importance of CI s in real life problems and comprehension of IFGs, we aim to develop some CI s in the environment of IFGs . We introduce two types of CI s, namely, CI and average CI, in the frame of IFGs . In spite of that, certain kinds of nodes called IF connectivity enhancing node IFCEN, IF connectivity reducing node IFCRN, and IF neutral node are introduced for IFGs . We have introduced strongest strong cycles, θ -evaluation of vertices, cycle connectivity, and CI of strong cycle. Applications of the CI s in two different types of networks are done, Internet routing and transport network flow, followed by examples to show the applicability of the proposed work.